Pengaruh Akses Air Minum Layak dan Akses Sanitasi Layak terhadap Tingkat Kemiskinan: Studi Panel Kabupaten di Jawa Barat Tahun 2020-2024 - Belia Dwi Putri; Muhammad Afdal Samsuddin (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to analyze the effect of access to clean drinking water and access to proper sanitation on poverty levels in 18 districts in West Java during 2020–2024. Using a quantitative approach and panel data regression, the study tested the relationship between the two independent variables and poverty as the dependent variable. The results of the analysis showed that access to clean drinking water had a negative and significant effect on poverty, with a regression coefficient of -0.05784 and a p-value of 0.0484 (<0.05). This means that every 1% increase in access to clean drinking water reduces the poverty rate by 0.05784%. Better access to clean water has a direct impact on reducing the economic burden and improving the welfare of the poor. Meanwhile, access to proper sanitation has a negative coefficient of -0.01350, but its effect is not statistically significant (p-value 0.3916> 0.05). This shows that although proper sanitation is important for quality of life and health, in this model its effect on poverty has not been seen to be directly significant. These findings emphasize the importance of expanding access to clean drinking water and sanitation as an effort to alleviate poverty in West Java. Limited access to basic services affects health, productivity, and household expenditure which ultimately worsens poverty. Therefore, local governments need to focus on inclusive and sustainable policies, especially improving basic services such as clean water and health. This study is expected to be a reference for formulating a more effective and comprehensive poverty alleviation strategy in West Java.